2017
DOI: 10.5489/cuaj.4471
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative nutritional factors and outcomes after radical cystectomy: A narrative review

Abstract: Only a few nutritional factors have been identified to predict the risk of developing complications after radical cystectomy (RC). This narrative review delineates the current known effects of preoperative nutritional status factors in this context. The report highlighted the heterogeneity between study methods and results. We determined that low albuminemia values increase mortality risk and overall complications. In addition, obesity tends to increase the risk of developing venous thromboembolism and adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The SNAP factors often co-exist and each add to the surgical risk [13][14][15]: about 50% for daily smoking, alcohol > 2 drinks/day [16] and severe malnutritionsimilar to the risks related to severe cardiac, pulmonary and kidney insufficiency. Obesity even at cancer surgery [17][18][19] and low physical activity are followed by 10-20% increase [20]. Frailty is an example of co-existing SNAP factors with a major impact on the surgical outcome [21,22].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
See 1 more Smart Citation
“…The SNAP factors often co-exist and each add to the surgical risk [13][14][15]: about 50% for daily smoking, alcohol > 2 drinks/day [16] and severe malnutritionsimilar to the risks related to severe cardiac, pulmonary and kidney insufficiency. Obesity even at cancer surgery [17][18][19] and low physical activity are followed by 10-20% increase [20]. Frailty is an example of co-existing SNAP factors with a major impact on the surgical outcome [21,22].…”
Section: Background and Rationale {6a}mentioning
confidence: 99%
“…General physical exercise reduces the postoperative recovery, but the impact on complications is disappointing [20,33,34]. Preoperative obesity and frailty interventions are still sparsely investigated in cancer surgery [18,[35][36][37].…”
Section: Need For a Combined Programmementioning
confidence: 99%
“…The primary exposure was pre-operative BMI, categorically operationalized in four strata according to the World Health Organization criteria: <18. 5…”
Section: Exposurementioning
confidence: 99%
“…1,3,4 Data regarding the effect of BMI on peri-operative complications are sparse with some evidence that patients with a low BMI have increased risk peri-operative complications, possibly relating to disease severity or poor nutrition. 5 Due to the conflicting data currently available, we sought to assess the association between patient BMI and morbidity and mortality associated with radical cystectomy. To do so, we utilized the American College of Surgeons (ACS) National Surgical Quality Improvement Program (NSQIP) database, a large, multi-institutional, validated registry that has been shown to perform better than administrative databases or institutional series in capturing intra-operative and post-operative complications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the association between malnutrition and poor surgical outcomes is well known. Several studies have shown that the presence of malnutrition biomarkers (e.g., low albumin, BMI, weight loss) increases the likelihood of post-RC complications [14][15][16][17]. In addition, severe wasting of skeletal muscle (sarcopenia) is predictive of oncologic and functional outcomes after RC [4,8,18,19].…”
Section: Introductionmentioning
confidence: 99%